Leadless pacemaker implant in the elderly: a safe and feasible solution. (14th October 2021) - Barletta, V; Parollo, M; Mazzocchetti, L; Giannotti Santoro, M; Canu, A; Sbragi, S; Di Cori, A; De Lucia, R; Segreti, L; Viani, S.M; Zucchelli, G; Bongiorni, M.G
Abstract: : The use of leadless pacing systems could overcome peri-and post-procedural complications related to the presence of transvenous leads and the post-operative recovery, being a favorable option in elderly patients. The study aimed to investigate feasibility and outcomes of M-TPS implant in a specific patient population, like the elderly, which represent a challenge for conventional cardiac pacing. Methods: Between May 2014 and March 2021, 138 patients (106 males, 77%, mean age 78) underwent M-TPS implantation in our Centre, targeting a non-apical site of delivery when feasible. A subgroup of 59 patients (43 males, 73%) were older than 80 years. All patients fulfilled standard criteria for pacemaker implantation with specific indication to receive VVI pacing. Study population was divided into two groups according to age (group 1 <80 years vs group 2 ≥80 years). The outcome evaluation included electrical performance (capture threshold, pacing impedance, R wave amplitude) before hospital discharge and then followed at 1, 6, and 12 months and then annually. Major complications were defined as life-threatening events, requiring surgical intervention or any event causing significant hemodynamic instability or resulting in death. High pacing threshold (HPT) was defined as >1.0 V@ 0.24 ms. Results: In 59/138 cases (43 males, 73%) M-TPS was implanted in patients older than 80 years. There were no statistically significant differences between groups for demographics characteristics, except for age, and PM implant indications. The implant procedure was successful in all cases and no device-related events were registered during follow-up. In particular, no device infection and/or malfunction were reported. Patients were followed-up for an average of 22, 19±20, 66 months (median 18 months). No differences were observed between groups in procedure duration (44, 97±20, 24 min vs 45, 80±23, 27 min; P=0, 83), single device delivery (group 1 vs group 2: 63, 16% vs 66, 07%; P=0, 73), fluoroscopy time (11, 64±6, 22 min vs 12, 13±8, 67 min; P=0, 72) electrical performance at implant [group 1 vs group 2: pacing threshold 0, 56±0, 37 vs 0, 58±0, 32, P=0, 78; impedance 727, 53±170, 36 vs 752, 88±256, 21, P=0, 49; R wave amplitude 10, 39±4, 86 vs 9, 26±4, 66, P=0, 18] and at median follow-up [group 1 vs group 2: pacing threshold 0, 63±0, 55 vs 0, 51±0, 1, P=0, 40; impedance 535, 34±102, 53 vs 577, 34±69, 02, P=0, 20; R wave amplitude 12, 56±4, 56 vs 12, 00±5, 80, P=0, 77] Conclusions: The demand for cardiac pacing is strongly related to ageing, driving the clinical practice to look for the best solution for a considered fragile population. MTP-S implant is an effective and safe procedure in elderly patients, with similar electrical performance and outcome compared with younger patients at mid-term follow-up. Funding Acknowledgement: Type of funding sources: None.